Harnessing Environmental Technology for Sustainable Healthcare: Innovations in Pollution Reduction and Health Risk Management - Omar, Mohammed Khaled Delph; Abdulrazzaq, Sarah Sabah; Zghair, Aqeel Abdul Hadi Shaalan; Kazim, Ali Sabbar Abdul Zahra; Saeed, Ismail Ibrahim Ahmed (American Journal of Biodiversity, 2025)
The increasing prevalence of chronic diseases and the environmental impact of healthcare operations have necessitated the integration of sustainable environmental technologies. However, there is still a knowledge gap regarding the effectiveness and implementation of pollution reduction strategies in healthcare settings. This study explores the role of environmental management technologies in reducing emissions, improving healthcare waste management, and mitigating health risks. Using a review-based methodology, various sustainable solutions, including emission control systems and waste treatment technologies, were analyzed. Findings indicate that these innovations significantly decrease pollution levels while maintaining healthcare efficiency. The results emphasize the need for regulatory frameworks and policy support to enhance environmental sustainability in healthcare institutions, ensuring long-term benefits for both public health and the environment.